Ecotoxicity tests using the green algae chlorella vulgaris — a useful tool in hazardous effluents management - Silva, Aurora (2013)
The treatment efficiency of laboratory wastewaters was evaluated and ecotoxicity tests with Chlorella vulgaris were performed on them to assess the safety of their environmental discharge. For chemical oxygen demand wastewaters, chromium (VI), mercury (II) and silver were efficiently removedby chemical treatments.Areduction of ecotoxicitywas achieved; nevertheless, an EC50 (effective concentration that causes a 50% inhibition in the algae growth) of 1.5% (v/v) indicated still high level of ecotoxicity. For chloride determination wastewaters, an efficient reduction of chromium and silver was achieved after treatment. Regarding the reduction of ecotoxicity observed, EC50 increased from 0.059% to 0.5%, only a 0.02% concentration in the aquatic environment would guarantee no effects. Wastewaters containing phenanthroline/iron (II) complex were treated by chemical oxidation. Treatmentwas satisfactory concerning chemical parameters, although an increase in ecotoxicitywas observed (EC50 reduced from 0.31% to 0.21%). The wastes from the kinetic study of persulphate and iodide reaction were treated with sodium bisulphite until colour was removed. Although they did not reveal significant ecotoxicity, only over 1% of the untreated waste produced observable effects over algae. Therefore, ecotoxicity tests could be considered a useful tool not only in laboratory effluents treatment, as shown, but also in hazardous wastewaters management.